Keanekaragaman Paku Terestrial di Kawasan Hutan dengan Tujuan Khusus (KHDTK) Yogyakarta - Yuskianti, Vivi; Rahayu, Siti Kholifah; Handayani, Trikinasih (Bioedukasi: Jurnal Pendidikan Biologi, 2018)
Ferns play an important role for humans and forest ecosystem. To know the diversity of ferns especially terrestrial ferns in Forest Area with Special Purpose (KHDTK) Kaliurang Yogyakarta, this research was conducted using entercept method in three study areas i.e. A with 876 m asl, B (899 m asl) and C (925 m asl). There were 20 stands for every study area and for each stand, the frequency frame equipment was placed 10 times with a total of 2000 times placing the equipment. This study found a total of 15 ferns from 7 family (Thelypteridacea, Sellaginellaceae, Polypodiaceae, Pteridaceae, Dryopteridacea, Marcileaceae dan Athyriaceae). In general, Parathelypteris japonica (Back.) Ching. from Thelypteridaceae family was the most dominant fern in KHDTK Kaliurang especially in A and B study area. The highest Important Value Index (INP) for the three study area was Parathelypteris japonica (68,76% ) while the lowest INP was Nephrolepis bisserata (Sw.) Schott (0,60%). The diversity index (H’) for KHDTK Kaliurang was low (0.15-0.27).